Binocular Coordination: Reading Stereoscopic Sentences in Depth - Schotter, Elizabeth R.; Blythe, Hazel I.; Kirkby, Julie A.; Rayner, Keith; Holliman, Nicolas S.; Liversedge, Simon P. (PLOS ONE, 2012)
The present study employs a stereoscopic manipulation to present sentences in three dimensions to subjects as they read for comprehension. Subjects read sentences with (a) no depth cues, (b) a monocular depth cue that implied the sentence loomed out of the screen (i.e., increasing retinal size), (c) congruent monocular and binocular (retinal disparity) depth cues (i.e., both implied the sentence loomed out of the screen) and (d) incongruent monocular and binocular depth cues (i.e., the monocular cue implied the sentence loomed out of the screen and the binocular cue implied it receded behind the screen). Reading efficiency was mostly unaffected, suggesting that reading in three dimensions is similar to reading in two dimensions. Importantly, fixation disparity was driven by retinal disparity; fixations were significantly more crossed as readers progressed through the sentence in the congruent condition and significantly more uncrossed in the incongruent condition. We conclude that disparity depth cues are used on-line to drive binocular coordination during reading.